SISTEM PAKAR PENYAKIT KESEHATAN MENTAL REMAJA MENGGUNAKAN METODE FORWARD CHAINING DAN CERTAINTY FACTOR - Eka Wahyu Sholeha; Billy Sabella; Wiwik Kusrini; Shanty Komalasari (Lambung Mangkurat University, 2023)
Mental health is something that every individual must have. It is important to understand about mental health from an early age, especially in adolescents. The initial diagnosis of mental health is currently still visiting a psychologist or psychiatrist. This is what makes teenagers feel embarrassed to visit a psychologist or psychiatrist. Expert systems can help diagnose mental health diseases early. Solving problems for early diagnosing adolescent mental health disorders using an expert system with the Forward Chaining and Certainty Factor methods. The research was aimed at adolescents in the South Kalimantan region. The expert data in this study were taken from a psychologist in Banjarbaru, South Kalimantan. The results showed that the Expert System for Adolescent Mental Health Diseases Using the Forward Chaining and Certainty Factor Methods had an accuracy rate of 86.67% of the 15 data held by experts, 13 data were the same as the system.Keywords: expert system, Forward Chaining, and Certainty Factor Kesehatan mental merupakan sesuatu yang pasti dimiliki oleh setiap individu. Pentingnya untuk memahami mengenai kesehatan mental sejak dini terutama pada remaja. Diagnosa awal kesehatan mental saat ini masih mengunjungi psikolog atau psikiater. Hal ini yang membuat remaja merasa malu untuk berkunjung ke psikolog atau psikiater. Sistem pakar dapat membantu mendiagnosa awal penyakit Kesehatan mental. Penyelesaian masalah untuk mendiagnosa secara dini gangguan kesehatan mental remaja menggunakan sistem pakar dengan metode Forward Chaining dan Certainty Factor. Penelitian ditujukan kepada remaja wilayah Kalimantan Selatan. Data pakar dalam penelitian diambil dari salah satu psikologi yang berada di Banjarbaru, Kalimantan Selatan. Hasil penelitian menunjukkan Sistem Pakar Penyakit Kesehatan Mental Remaja Menggunakan Metode Forward Chaining dan Certainty Factor memiliki tingkat akurasi yaitu 86,67% dari 15 data yang dimiliki pakar, 13 data sama dengan sistem. Kata kunci: sistem pakar, Forward Chaining, dan Certainty Factor